Catabolism of protocatechuate by Bacillus macerans. - Crawford, R L (1979)
An aerobic endospore-forming bacterium, tentatively identified as a strain (JJ-lb) of Bacillus macerans, was isolated by enrichment on 4-hydroxybenzoate (4HBA), using as an inoculum soil taken from a 50 degrees C Iadho hot spring. Enzymatic analyses of cells grown on succinate and 4HBA indicated that strain JJ-1b degrades 4HBA by way of the novel protocatechuate (PCA) 2,3-dioxygenase pathway. Purification of the PCA 2,3-dioxygenase by affinity chromatography allowed the first observation of the immediate ring fission product of PCA, namely, 5-carboxy-2-hydroxymuconic semialdehyde (CHMS; labmda max at pH 7.0 = 348 nm). An affinity column fraction was obtained that decarboxylated CHMS to 2-hydroxymuconic semialdehyde (HMS; lambdamax at pH 7.0 = 375 nm). Thus, conversion of PCA to HMS is accomplished in two steps, 2,3-fission of the PCA ring followed by enzymatic decarboxylation of the ring fission product, forming HMS.